Wonderful Indonesia Campaign As Indonesia’s Nation Branding On Digital Media - Rosadi, Raesita Rakhmawati; Wiradharma, Gunawan; Arisanty, Melisa (Universitas Islam Negeri Raden Intan Lampung, 2022)
Social media’s influence on purchasing decisions is on the radar of a multitude of industries worldwide and the tourism industry is no exception. Social media today is become a tool for countries in the world to promote tourism in their countries. Nation branding is a method for countries to differentiate and distinguish themselves from other countries around the world through branding. This phenomenon allowing countries to compete with each other to attract tourist from all over the world. Thus, every country needs special identity and uniqueness that differ a country from another. Indonesia is one of many countries that have been started a nation branding campaign that called ‘Wonderful Indonesia’ in 2011. Head of Ministry of Tourism of Republic Indonesia Arief Yahya stated that, in 2020 Indonesia have targeted 20 million of foreign tourists to come to Indonesia with a projected foreign exchange earnings of 18.5 billion USD (kemenpar.go.id). This study found that Wonderful Indonesia Campaign has been communicated through digital media (Website, Facebook, Instagram, Twitter, and YouTube). This study describes the channels that were utilized to promote the campaign and gives inputs to optimize the technical and content used in the campaign media.